The old youthful ghost: The Costa Rican high school student as a political subject - Calderón Méndez, Rafael (2025)
Young political activism and its impact on social change in Costa Rica are not foreign to academic discussion. However, the figure of the young high school student has been relegated to a few sporadic mentions and to positions that indicate a lack of or negligible relevance and significance. This creates an image of students as an apathetic and apolitical mass. The present essay proposes a reflective exercise: to think of the high school students as a political subject. For this, the theoretical, conceptual, and methodological route is framed by the notions of field and agent from Pierre Bourdieu’s constructivist structuralism. The objective of the discussion presented here is to generate an approach to understand the positions, the production of discourse, and the action of the subject in the political field, from general historiographical perspective of the student and the educational system in which he/she is situated.